Systemic mastocytosis presenting with gastrointestinal, bone and skin involvement - Rosignuolo, Maria (J Ultrasound, 2014)
Ultrasonography (US) is often the first imaging study performed in patient with abdominal pain or vague symptoms related to the gastrointestinal tract. To this end, it has been demonstrated that transabdominal sonography achieves good to excellent results in potential bowel disorders; especially, if ultrasonography findings are framed in the context of clinical information. Systemic mastocytosis is not a common disease and it usually involves skin, gastrointestinal tract and bone. It results from a clonal neoplastic proliferation of abnormal mast cells and clinically it can ranges from ‘asymptomatic’ with normal life expectancy to ‘highly aggressive’. Symptoms are caused by the release of mast cells mediators, such as histamine, and by the increase bulk of mast cells in the tissue. We present herein a case of systemic mastocytosis presenting with abdominal symptomatology due to thickened colonic involvement showed by US associated with bone and skin involvement.